RANCANGAN SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS WEB PADA SMK PUTRA RIFARA - Ainiyatul Maghfiroh; Henderi Henderi; Giandari Maulani (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
New student registration is one of the processes that is normally carried out every year in educational institutions such as schools. New student registration is useful for screening prospective students who have been selected tobecome their students. In this research the process of registering new students at SMK Putra Rifara is done conventionally and has not been computerized, which allows many errors from writing data, stacking files and losing data. The formulation of the problem of this research is how to make a registration information system for SMK Putra Rifara. So the research method used is the method of observation, interviews, and library methods. The new student registration in formation system is buit with the PHP programming language and utilizes the MySQL database as a database server. The results of this study are web-based new student registration information systems that have the ability to provide data accuracy and ease for parents and prospective new students to obtain information about the school.